2000
DOI: 10.1021/ic000295h
|View full text |Cite
|
Sign up to set email alerts
|

The Propionate of Heme Binds N4O2 Schiff Base Antimalarial Drug Complexes

Abstract: Schiff base N4O2 complexes offer a flexible template on which to develop novel antimalarial drug complexes that inhibit the aggregation of hemozoin, a detoxification product of the malaria parasite Plasmodium falciparum. The efficacies of these complexes are dependent on the charges of the complexes. Further evidence suggests that these complexes inhibit hemozoin formation via a specific drug/heme propionate salt that prevents the formation of the requisite axial propionato linkage in the repeating dimeric uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…The power of these concepts has recently been demonstrated by Marletta and coworkers, who employed HRP II-mediated formation of hemozoin as a screen against which to test new libraries of compounds for antimalarial activity [99]. Similarly, Wright and coworkers have used their bionucleating templates as a proxy for HRP II to examine the mode of efficacy of a number of different classes of inhibitors, including other metalloporphyrins [100] and Scheme 2 Potential inhibition pathways to hemozoin aggregation unique Schiff-base metallodrugs [101]. In each of these cases, inhibitors that act in all of the imagined functions have been discovered that may one day result in new treatments for malaria.…”
Section: Discussionmentioning
confidence: 99%
“…The power of these concepts has recently been demonstrated by Marletta and coworkers, who employed HRP II-mediated formation of hemozoin as a screen against which to test new libraries of compounds for antimalarial activity [99]. Similarly, Wright and coworkers have used their bionucleating templates as a proxy for HRP II to examine the mode of efficacy of a number of different classes of inhibitors, including other metalloporphyrins [100] and Scheme 2 Potential inhibition pathways to hemozoin aggregation unique Schiff-base metallodrugs [101]. In each of these cases, inhibitors that act in all of the imagined functions have been discovered that may one day result in new treatments for malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the minimal hemozoin aggregation assay system employed, a readily envisioned mechanism for these complexes is that they interact with either the propionate moieties of the porphyrin ligand or the aspartic acid side chains of the BNT II template. Fluorescence quenching experiments revealed that under assay conditions, the drugs did not appreciable interact with the template (36). In contrast, Fe(III)PPIX quenched the weak fluorescence of the Fe(III) and Ga(ill) ENBPI analogues, suggesting interaction between heme substrate and the inhibitor.…”
Section: N 4 0 2 Coordination Complexesmentioning
confidence: 93%
“…When the acetate buffer concentration increased from 25 mM to 500 mM, the IC 50 of the complexes increased until they no longer inhibited hemozoin aggregation. A control series of experiments performed at 25 mM acetate buffer concentration with increasing concentrations of NaCl revealed no effect on die IC 50 values of the complexes (36). This suggested that the interactions between the drug complexes and heme propionate are not simple salt interactions, but specific to the carboxylate moiety.…”
Section: N 4 0 2 Coordination Complexesmentioning
confidence: 94%
See 1 more Smart Citation
“…Transition metal salicylaldimines (salen-type) have been studied broadly due to their significance as biomimetic models for metaloproteins, effective catalysts for oxygenation processes and utilization in asymmetric catalysis, as building blocks for the self-assembly of helicates, and as antimalarial drugs [1][2][3][4][5][6][7][8][9]. X-ray structure data reveal that in the d-block metal complexes of this type, the Schiff bases generally act as deprotonated tetradentate ligands with the N 2 O 2 set of donor atoms capable of effective coordination in the planar fashion.…”
mentioning
confidence: 99%